Etching agent combination and application method for improving metallographic structure visualization effect
Through the combination of double-layer synergistic corrosion agents, the problem that traditional corrosion agents are difficult to achieve uniform corrosion on metal surfaces is solved, and the clearness and consistency of metallographic structure is shown, which improves the accuracy and reliability of metallographic analysis.
Patent Information
- Application Number
- CN202411227061.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-03
- Publication Date
- 2025-04-01
AI Technical Summary
Traditional metallographic structures show that corrosion agents are difficult to achieve uniform corrosion on the metal surface during application, resulting in local excessive corrosion or insufficient corrosion, affecting the accuracy of the analysis.
Using a combination of two-layer synergistic corrosion agents, the first layer of corrosion agents includes alcohol nitric acid, sodium fluoride solution and ammonium chloride solution, and the second layer of corrosion agents includes hydrofluoric acid, hydrochloric acid, sulfuric acid and ethanol. Combining inhibitors, complexing agents and surfactants, the metal phase structure is revealed through a finely designed multi-layer corrosion process.
It significantly improves the uniformity of the corrosion process, ensures that all parts of the metallographic structure are consistent and clear, reduces the problems of local excessive corrosion or insufficient corrosion, and improves the accuracy and reliability of metallographic analysis.
Smart Images

Figure CN119738240A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of metallographic analysis, in particular to a combination of corrosive agents for improving the metallographic structure visualization effect and an application method thereof. Background Art
[0002] Metallographic structure visualization is a crucial analytical technique in the field of materials science and engineering, and is widely used to study the microstructure of metal materials. Through appropriate corrosion techniques, the grain structure, phase distribution, precipitates and other microscopic characteristics inside the material can be revealed, and this information is of great significance for understanding the performance, quality control and failure analysis of the material. However, existing metallographic structure visualization etchants and methods have some significant shortcomings and limitations in practical applications.
[0003] However, it is often difficult to achieve uniform corrosion on the metal surface during the application of traditional corrosive agents. Due to the unstable composition or reaction conditions of the corrosive agent, it may cause local excessive corrosion or insufficient corrosion, resulting in deviations in the metallographic structure and affecting the accuracy of the analysis. Summary of the invention
[0004] In view of the deficiencies in the prior art, the present invention provides a combination of corrosive agents and an application method for improving the metallographic structure visualization effect, thereby solving the problem that traditional corrosive agents may cause local excessive corrosion or insufficient corrosion during the application process, resulting in deviations in the visualized metallographic structure and affecting the accuracy of the analysis.
[0005] To achieve the above object, the present invention is implemented by the following technical scheme: an etchant combination for improving the metallographic structure display effect comprises:
[0006] The first layer of corrosive agent includes nitric acid alcohol, sodium fluoride solution, ammonium chloride solution, and the balance is distilled water;
[0007] The second layer of etchant includes hydrofluoric acid, hydrochloric acid, sulfuric acid, and the balance is ethanol;
[0008] Additional ingredients include inhibitors, complexing agents, and surfactants.
[0009] Preferably, the nitrate alcohol is 3%-5%, the sodium fluoride solution is 1%-3%, and the ammonium chloride solution is 2%-4%;
[0010] The hydrofluoric acid is 0.2%-0.8%, the hydrochloric acid is 1%-2%, and the sulfuric acid is 0.5%-1.5%;
[0011] The inhibitor is benzotriazole, the addition amount is 0.1%-0.3%, the complexing agent is ethylenediaminetetraacetic acid, the addition amount is 0.5%-1.5%, and the surfactant is sodium dodecyl sulfate, the addition amount is 0.2%-0.5%.
[0012] Preferably, the method for preparing the first layer of corrosive agent comprises the following steps:
[0013] Step 1: Slowly add nitric acid to ethanol and stir gently until uniform;
[0014] Step 2: Take distilled water and dissolve sodium fluoride and ammonium chloride;
[0015] Step 3: Mix the two to make the first layer of corrosive agent. Keep the temperature low during the mixing process to prevent sodium fluoride and ammonium chloride from reacting prematurely.
[0016] Preferably, the ethanol in step 1 is 90 mL-110 mL, and the added nitric acid is 3 mL-5 mL;
[0017] The distilled water in step 2 is 90 mL-110 mL, and the dissolved sodium fluoride and ammonium chloride are 1 g-3 g and 2 g-4 g respectively;
[0018] In the step 3, the temperature is controlled within the range of 10°C-15°C.
[0019] Preferably, the method for preparing the second layer of the corrosive agent comprises the following steps:
[0020] Step 1: Add hydrofluoric acid, hydrochloric acid and sulfuric acid to ethanol in sequence and stir slowly until uniform;
[0021] Step 2: Add inhibitor, complexing agent and surfactant and continue stirring until completely dissolved.
[0022] Preferably, in step 1, the amount of ethanol is 90 mL-110 mL, the amount of hydrofluoric acid is 0.2 mL-0.8 mL, the amount of hydrochloric acid is 1 mL-2 mL, and the amount of sulfuric acid is 0.5 mL-1.5 mL.
[0023] Preferably, the method for applying the combination of etchants to improve the metallographic structure visualization effect comprises the following steps:
[0024] Step 1: Sample preparation
[0025] Select the metal sample to be tested, including high alloy steel, titanium alloy or aluminum alloy;
[0026] Use sandpaper to gradually grind the surface of the specimen to remove all oxide layers and surface defects, and finally perform mirror polishing;
[0027] Step 2: First layer of corrosion
[0028] Immerse the polished metal sample in the first layer of corrosive agent. During the corrosion process, gently shake the sample to make the corrosive agent evenly cover the entire surface of the metal sample.
[0029] After taking out the sample, immediately rinse it with a large amount of distilled water to remove the corrosive agent residue; then wipe it dry with a lint-free cloth or blow it dry with air;
[0030] Step 3: Second layer of corrosion
[0031] Immerse the sample after the first layer of corrosion in the second layer of corrosive agent. Also, gently shake the sample during the corrosion process to ensure uniform contact and reaction of the corrosive agent.
[0032] After the sample was taken out, it was immediately washed with distilled water to remove the corrosive agent and reaction products, and finally rinsed with anhydrous ethanol and then dried with hot air.
[0033] Preferably, in step 1, sandpaper with mesh size of 600-1200 is used;
[0034] In the step 2, the corrosion time is controlled within 5 seconds to 15 seconds;
[0035] In the step 3, the soaking time is 3 seconds to 10 seconds.
[0036] The invention provides an etchant combination for improving the metallographic structure revealing effect and an application method.
[0037] It has the following beneficial effects:
[0038] 1. The double-layer synergistic etchant combination provided by the present invention significantly improves the uniformity of the corrosion process through the synergistic effect of multiple components that are cleverly designed. On the metal surface, the etchant can form a stable and uniform corrosion layer, ensuring that all parts of the metallographic structure are consistently and clearly displayed. This uniform corrosion effect greatly reduces the problem of local excessive corrosion or insufficient corrosion, thereby significantly improving the accuracy and reliability of metallographic analysis.
[0039] 2. The etching agent combination of the present invention is specially designed with a multi-level etching process. By selectively exposing and showing different metallographic phases, the microstructural contrast is greatly enhanced. The sample after etching shows clearer grain boundaries and organizational features under the microscope, which is particularly suitable for the analysis of complex multiphase materials.
[0040] 3. The etchant combination of the present invention has good versatility and is applicable to a variety of metal materials including high alloy steel, titanium alloy, and aluminum alloy. This combination can flexibly respond to the display requirements of different materials by adjusting the concentration and application parameters of the etchant, greatly improving the adaptability and practicality of the etchant and reducing the debugging workload of the experimenter.
[0041] 4. The present invention adopts an optimized component ratio and preparation method, which makes the corrosive agent more stable during preparation, storage and use, and reduces the risk of decomposition or failure of the corrosive agent. At the same time, inhibitors, complexing agents and surfactants are added to further improve the safety of the corrosive agent and reduce the potential harm to operators and the environment during the experiment. BRIEF DESCRIPTION OF THE DRAWINGS
[0042] Figure 1 is a flow chart of a method for preparing a first layer of an etchant according to the present invention;
[0043] Figure 2 is a flow chart of a method for preparing the second layer of the etchant of the present invention;
[0044] Figure 3 The present invention is a flow chart of the application method of the etching agent combination for improving the metallographic structure visualization effect. DETAILED DESCRIPTION
[0045] The technical solution of the present invention will be described clearly and completely below in conjunction with the accompanying drawings of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0046] Please see attached Figure 1 - Attachment Figure 3 The embodiment of the present invention provides an etchant combination for improving the metallographic structure visualization effect, comprising:
[0047] First layer of corrosive agent:
[0048] Nital: Used for preliminary etching of metal surfaces to expose the macroscopic structure. Nital concentrations range from 3% to 5%, which is able to effectively oxidize the metal surface and reveal the grain structure.
[0049] Sodium fluoride solution: As an oxidation stabilizer in the corrosion process, the concentration range is 1%-3%. Sodium fluoride can control the reaction rate, prevent excessive corrosion, and ensure a uniform corrosion effect.
[0050] Ammonium chloride solution: The concentration range is 2%-4%. Its function is to enhance the uniformity of corrosion and improve the contrast of metallographic structure, making the appearance of different phases clearer.
[0051] Second layer of corrosive agent:
[0052] Hydrofluoric acid: Mainly used for fine corrosion, so that microstructures such as grain boundaries and precipitated phases can be revealed. The concentration range of hydrofluoric acid is 0.2%-0.8%.
[0053] Hydrochloric acid: As a cleaning agent, it is used to remove surface oxides and further dissolve impurities on the metal surface, with a concentration range of 1%-2%.
[0054] Sulfuric acid: Concentration range is 0.5%-1.5%, used to increase the depth of corrosion so that the details of the metal can be fully revealed.
[0055] Ethanol: As a solvent, the concentration of ethanol is controlled at 90%-95%, which plays a role in regulating the reaction rate and solubility during the corrosion process.
[0056] Additional Ingredients:
[0057] Inhibitor (Benzotriazole): Concentration of 0.1%-0.3%, used to prevent excessive corrosion of certain metal alloy components, ensure the selectivity of corrosion, and especially protect sensitive areas in the material.
[0058] Complexing agent (ethylenediaminetetraacetic acid, EDTA): The concentration is 0.5%-1.5%, which is used to chelate the metal ions released during the corrosion process, prevent these ions from depositing on the surface of the sample to form secondary pollutants, and maintain the cleanliness of the corrosion.
[0059] Surfactant (sodium dodecyl sulfate, SDS): The concentration is 0.2%-0.5%, which is used to improve the uniformity of the distribution of the corrosive agent on the metal surface, ensure the overall consistency of the corrosion process, and avoid excessive or uneven local corrosion.
[0060] The method for preparing the first layer of etching agent comprises the following steps:
[0061] Step 1: Preparation of Nitrate
[0062] Slowly add 3mL-5mL nitric acid to 90mL-110mL ethanol. Stir gently to ensure that the nitric acid is evenly dissolved in the ethanol to form a uniform nitric acid alcohol solution.
[0063] Pay attention to controlling the addition speed to prevent excessive reaction and ensure the stability of the solution.
[0064] Step 2: Dissolution of sodium fluoride and ammonium chloride
[0065] Take another 90mL-110mL of distilled water and dissolve 1g-3g of sodium fluoride and 2g-4g of ammonium chloride in the water. Stir until completely dissolved and ensure that no solid remains.
[0066] To prevent side reactions during the dissolution process, the process should be carried out in a clean environment and deionized water or high-purity distilled water should be used.
[0067] Step 3: Mixing and temperature control
[0068] Combine the nitrate alcohol solution with the mixed solution of sodium fluoride and ammonium chloride. During this process, the temperature needs to be controlled within the range of 10°C-15°C to prevent the sodium fluoride and ammonium chloride from reacting prematurely, thereby maintaining the activity and stability of the solution.
[0069] When mixing, use an ice bath or cooling water tank to ensure a low temperature environment and stir slowly until the solution is completely mixed.
[0070] The method for preparing the second layer of the corrosive agent comprises the following steps:
[0071] Step 1: Preparation of basic etchant
[0072] Add 0.2mL-0.8mL hydrofluoric acid, 1mL-2mL hydrochloric acid and 0.5mL-1.5mL sulfuric acid to 90mL-110mL ethanol in sequence and stir slowly until the solution is uniform. Good ventilation should be maintained during the operation, and the operator should wear protective equipment to ensure safety.
[0073] Each time the acidic component is added, it should be done slowly to ensure complete dissolution to prevent solution stratification or precipitation caused by local over-acidity.
[0074] Step 2: Adding additional ingredients
[0075] Add 0.1%-0.3% benzotriazole (inhibitor), 0.5%-1.5% EDTA (chelating agent) and 0.2%-0.5% SDS (surfactant) to the prepared basic etchant, and continue stirring until completely dissolved to ensure that all ingredients are evenly distributed in the solution.
[0076] When adding additional ingredients, continue stirring and ensure that the solution remains uniform to avoid adverse reactions between ingredients.
[0077] The application method of the etchant combination for improving the metallographic structure visualization effect comprises the following steps:
[0078] Step 1: Sample preparation
[0079] Material selection: Select the appropriate specimen according to the type of metal to be tested (such as high alloy steel, titanium alloy or aluminum alloy).
[0080] Grinding and polishing: Use 600-1200 mesh sandpaper to gradually grind the sample surface to remove all oxide layers and surface defects, and finally perform mirror polishing to ensure that the surface is smooth and scratch-free. Pay attention to even force during operation to ensure that there are no obvious dents or scratches on the surface after grinding.
[0081] Step 2: First layer of corrosion
[0082] Immersion corrosion: Immerse the polished metal sample in the prepared first layer of corrosive agent, and control the corrosion time to 5 seconds to 15 seconds. Gently shake the sample to make the corrosive agent evenly cover the metal surface to ensure the uniformity of the corrosion process.
[0083] Cleaning and drying: After taking out the sample, immediately rinse it with plenty of distilled water to remove the corrosive agent residue. Use a lint-free cloth to wipe the sample dry or blow it dry with air to ensure that there are no water marks or other residues.
[0084] Step 3: Second layer of corrosion
[0085] Fine etching: Soak the sample after the first layer of etching in the second layer of etching agent, and control the immersion time to 3 seconds to 10 seconds. Also, gently shake the sample during the etching process to ensure uniform contact and reaction of the etching agent.
[0086] Final cleaning and drying: After removing the sample, immediately rinse it thoroughly with distilled water to remove the corrosive agent and reaction products. Then use anhydrous ethanol for the final rinse to ensure that there is no residue on the surface. Use hot air to dry it to avoid moisture residue affecting microscopic observation.
[0087] The following is an introduction in conjunction with specific embodiments:
[0088] Example 1
[0089] First layer of corrosive agent:
[0090] Nitrate: 4%
[0091] Sodium fluoride solution: 2%
[0092] Ammonium chloride solution: 3%
[0093] Ethanol: 100mL
[0094] Distilled water: 95 mL
[0095] Second layer of corrosive agent:
[0096] Hydrofluoric acid: 0.5%
[0097] Hydrochloric acid: 1.5%
[0098] Sulfuric acid: 1%
[0099] Ethanol: 100mL
[0100] Additional Ingredients:
[0101] Inhibitor (benzotriazole): 0.2% Complexing agent (EDTA): 1%
[0102] Surfactant (SDS): 0.3% Application parameters:
[0103] First layer corrosion time: 10 seconds
[0104] Second layer corrosion time: 7 seconds Mixing temperature: 12°C Example 2
[0105] First layer of corrosive agent:
[0106] Nitrate: 3.5%
[0107] Sodium fluoride solution: 1.5%
[0108] Ammonium chloride solution: 2.5%
[0109] Ethanol: 105mL
[0110] Distilled water: 100 mL
[0111] Second layer of corrosive agent:
[0112] Hydrofluoric acid: 0.3%
[0113] Hydrochloric acid: 1.2%
[0114] Sulfuric acid: 0.8%
[0115] Ethanol: 110mL
[0116] Additional Ingredients:
[0117] Inhibitor (benzotriazole): 0.1% Complexing agent (EDTA): 0.7%
[0118] Surfactant (SDS): 0.4% Application parameters:
[0119] First layer of corrosion time: 12 seconds
[0120] Second layer corrosion time: 5 seconds Mixing temperature: 14°C Example 3
[0121] First layer of corrosive agent:
[0122] Nitrate: 5%
[0123] Sodium fluoride solution: 3%
[0124] Ammonium chloride solution: 4%
[0125] Ethanol: 90mL
[0126] Distilled water: 110 mL
[0127] Second layer of corrosive agent:
[0128] Hydrofluoric acid: 0.6%
[0129] Hydrochloric acid: 1.8%
[0130] Sulfuric acid: 1.2%
[0131] Ethanol: 95mL
[0132] Additional Ingredients:
[0133] Inhibitor (benzotriazole): 0.3% Complexing agent (EDTA): 1.2%
[0134] Surfactant (SDS): 0.5% Application parameters:
[0135] First layer of corrosion time: 7 seconds
[0136] Second layer corrosion time: 8 seconds Mixing temperature: 10°C Example 4
[0137] First layer of corrosive agent:
[0138] Nitrate: 4.5%
[0139] Sodium fluoride solution: 2.8%
[0140] Ammonium chloride solution: 3.5%
[0141] Ethanol: 95mL
[0142] Distilled water: 100 mL
[0143] Second layer of corrosive agent:
[0144] Hydrofluoric acid: 0.4%
[0145] Hydrochloric acid: 1.4%
[0146] Sulfuric acid: 1.1%
[0147] Ethanol: 100mL
[0148] Additional Ingredients:
[0149] Inhibitor (benzotriazole): 0.15% Complexing agent (EDTA): 0.9%
[0150] Surfactant (SDS): 0.25%
[0151] Application parameters:
[0152] First layer of corrosion time: 9 seconds
[0153] Second layer corrosion time: 6 seconds Mixing temperature: 11°C Table 1 Corrosion properties of different embodiments
[0154]
[0155]
[0156] Among them, the table fields are explained as follows:
[0157] Corrosion depth: describes the depth of corrosion caused by the corrosive agent on the surface of the metal sample. Surface uniformity: refers to the flatness and consistency of the metal surface after corrosion. Higher uniformity indicates a more consistent corrosion effect.
[0158] Microstructural contrast: refers to the visual difference between different parts of the metallographic structure when observed under a microscope. Higher contrast helps to distinguish different tissues more clearly.
[0159] Grain structure appearance: describes the clarity of grain boundaries after etching.
[0160] Corrosion rate control: refers to the difficulty of controlling the speed during the corrosion process. A corrosion rate with high stability is easier to control the final effect.
[0161] Surface residue: refers to the corrosion byproducts remaining on the surface of the sample after corrosion.
[0162] Surface roughness: describes the roughness of the metal surface after corrosion, affecting microscopic observation and subsequent processing.
[0163] Applicable materials: Indicate which metal materials the corrosion treatment of this embodiment is applicable to.
[0164] The degree of detail revealed by the microstructure: reflects the ability of the corrosive agent combination to reveal the microscopic details of the metallographic structure.
[0165] Microscope observation effect after corrosion: Comprehensively evaluate the overall observation effect of the sample under the microscope after corrosion.
[0166] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. A combination of etchants for improving the metallographic structure visualization effect, characterized in that: include: The first layer of corrosive agent includes nitric acid alcohol, sodium fluoride solution, ammonium chloride solution, and the balance is distilled water; The second layer of etchant includes hydrofluoric acid, hydrochloric acid, sulfuric acid, and the balance is ethanol; Additional ingredients include inhibitors, complexing agents, and surfactants.
2. The etching agent combination for improving the metallographic structure visualization effect according to claim 1, characterized in that: The nitrate alcohol is 3%-5%, the sodium fluoride solution is 1%-3%, and the ammonium chloride solution is 2%-4%; The hydrofluoric acid is 0.2%-0.8%, the hydrochloric acid is 1%-2%, and the sulfuric acid is 0.5%-1.5%; The inhibitor is benzotriazole, the addition amount is 0.1%-0.3%, the complexing agent is ethylenediaminetetraacetic acid, the addition amount is 0.5%-1.5%, and the surfactant is sodium dodecyl sulfate, the addition amount is 0.2%-0.5%.
3. The etching agent combination for improving the metallographic structure visualization effect according to claim 1, characterized in that: The method for preparing the first layer of the corrosive agent comprises the following steps: Step 1: Slowly add nitric acid to ethanol and stir gently until uniform; Step 2: Take distilled water and dissolve sodium fluoride and ammonium chloride; Step 3: Mix the two to make the first layer of corrosive agent. Keep the temperature low during the mixing process to prevent sodium fluoride and ammonium chloride from reacting prematurely.
4. The etching agent combination for improving the metallographic structure visualization effect according to claim 3, characterized in that: The ethanol in step 1 is 90 mL-110 mL, and the added nitric acid is 3 mL-5 mL; The distilled water in step 2 is 90 mL-110 mL, and the dissolved sodium fluoride and ammonium chloride are 1 g-3 g and 2 g-4 g respectively; In the step 3, the temperature is controlled within the range of 10°C-15°C.
5. The etching agent combination for improving the metallographic structure visualization effect according to claim 1, characterized in that: The method for preparing the second layer of the corrosive agent comprises the following steps: Step 1: Add hydrofluoric acid, hydrochloric acid and sulfuric acid to ethanol in sequence and stir slowly until uniform; Step 2: Add inhibitor, complexing agent and surfactant and continue stirring until completely dissolved.
6. The etching agent combination for improving the metallographic structure visualization effect according to claim 5, characterized in that: In the step 1, the amount of ethanol is 90 mL-110 mL, the amount of hydrofluoric acid is 0.2 mL-0.8 mL, the amount of hydrochloric acid is 1 mL-2 mL, and the amount of sulfuric acid is 0.5 mL-1.5 mL.
7. A method for applying a combination of etchants to improve the metallographic structure visualization effect, characterized in that: The etching agent combination for improving the metallographic structure visualization effect according to any one of claims 1 to 6 comprises the following steps: Step 1: Sample preparation Select the metal sample to be tested, including high alloy steel, titanium alloy or aluminum alloy; Use sandpaper to gradually grind the surface of the specimen to remove all oxide layers and surface defects, and finally perform mirror polishing; Step 2: First layer of corrosion Immerse the polished metal sample in the first layer of corrosive agent. During the corrosion process, gently shake the sample to make the corrosive agent evenly cover the entire surface of the metal sample. After taking out the sample, immediately rinse it with a large amount of distilled water to remove the corrosive agent residue; then wipe it dry with a lint-free cloth or blow it dry with air; Step 3: Second layer of corrosion Immerse the sample after the first layer of corrosion in the second layer of corrosive agent. Also, gently shake the sample during the corrosion process to ensure uniform contact and reaction of the corrosive agent. After the sample was taken out, it was immediately washed with distilled water to remove the corrosive agent and reaction products, and finally rinsed with anhydrous ethanol and then dried with hot air.
8. The method for applying the combination of etchants for improving the metallographic structure visualization effect according to claim 7, characterized in that: In the step 1, sandpaper with mesh size of 600-1200 is used; In the step 2, the corrosion time is controlled within 5 seconds to 15 seconds; In the step 3, the soaking time is 3 seconds to 10 seconds.
Citation Information
Cited By
Preparation method of metallographic test sample of high-purity metal
CN121141302A
CrMoTa series refractory high-entropy alloy metallographic etchant and preparation method thereof
CN122105407A